Jurnal Penyuluhan: Pengaruh Modal Sosial terhadap Ketahanan Pangan Rumahtangga Petani di Desa Ciaruteun Ilir Kecamatan Cibungbulang Kabupaten Bogor - Sara Endarwati, Ekawati Sri Wahyuni (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Social capital is an important component in a community. Social capital is used to help each other when in need, such as the need to secure food sufficiency in a household. Social capital consists of trust, networks, and social norms.